2004
DOI: 10.1098/rspb.2004.2741
|View full text |Cite
|
Sign up to set email alerts
|

Elevated testosterone reduces choosiness in female dark–eyed juncos (Junco hyemalis): evidence for a hormonal constraint on sexual selection?

Abstract: Because testosterone (T) often mediates the expression of attractive displays and ornaments, in the absence of constraints sexual selection should lead to an evolutionary increase in male T levels. One candidate constraint would be a genetic correlation between the sexes that leads to a correlated response in females. If increased T in females were to have deleterious effects on mate choice, the effect of sexual selection on male T would be weakened. Using female dark-eyed juncos ( Junco hyemalis), we tested w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…They have been explored mainly in the field of sexual selection (e.g. Clotfelter et al 2004;McGlothlin et al 2004), but they are probably important in other contexts of functional differentiation of males and females (e.g. Temeles et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been explored mainly in the field of sexual selection (e.g. Clotfelter et al 2004;McGlothlin et al 2004), but they are probably important in other contexts of functional differentiation of males and females (e.g. Temeles et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the amount of work investigating the relations between behavioural phenotypes within honeybee workers, correlations across castes or sexes have not been addressed (but see Giray & Robinson 1996), even though male-female correlations are of general importance to understand the evolution of animal behaviour (Price & Langen 1992;McGlothlin et al 2004). Male honeybees (drones) serve an exclusively reproductive function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not been well studied, however, whether these changes in receptive behavior are accompanied by changes in the range of mate signals that female will accept. In one recent study, testosterone-treated female dark-eyed juncos (Junco hyemalis) were less discriminating in their mate choices than control females (McGlothlin et al, 2004). Although there are few hormone manipulation studies that provide empirical support for these predictions, it has been shown that variation in mate choice decisions can be associated with changes in reproductive stage (Lea et al, 2000;Bosch and Boyero, 2004;, and that, in a few anuran species, changes in reproductive stage are associated with changes in hormonal state (Licht et al, 1983;Pierantoni et al, 1984;Iela et al, 1986;Itoh and Ishii, 1990;Harvey et al, 1997;Medina et al, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…In many species, testosterone in females is also strongly correlated with territorial aggression. 38,39,40 Do aggressive responses depend on STI?…”
Section: Do Baseline T and Aggressive Behavior Covary Among Individuals?mentioning
confidence: 99%